2017 IEEE 20th International Conference on Intelligent Transportation Systems (ITSC) 2017
DOI: 10.1109/itsc.2017.8317943
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic vehicle trajectory prediction over occupancy grid map via recurrent neural network

Abstract: In this paper, we propose an efficient vehicle trajectory prediction framework based on recurrent neural network. Basically, the characteristic of the vehicle's trajectory is different from that of regular moving objects since it is affected by various latent factors including road structure, traffic rules, and driver's intention. Previous state of the art approaches use sophisticated vehicle behavior model describing these factors and derive the complex trajectory prediction algorithm, which requires a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
175
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(190 citation statements)
references
References 12 publications
2
175
0
Order By: Relevance
“…LSTM can infer goals with a relatively high accuracy in a wide range of activities of daily living with similar situations. Further, a number of advantages of LSTM model for goal prediction, especially in dynamic environment like the smart home, were identified that are consistent with past research (Bai et al, 2018;Kim et al, 2017;Lipton et al, 2016;Peng & Lin, 2016).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…LSTM can infer goals with a relatively high accuracy in a wide range of activities of daily living with similar situations. Further, a number of advantages of LSTM model for goal prediction, especially in dynamic environment like the smart home, were identified that are consistent with past research (Bai et al, 2018;Kim et al, 2017;Lipton et al, 2016;Peng & Lin, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…It is important to note that the behavior of the gate control is data driven (i.e., learned from data). Also, an additional output network is added to the hidden state h t , this enables us to extract the information relevant to the given problem (Kim et al, ) . For example, since our case study is formulated as a multi‐class classification problem (see Figure ), to obtain the prediction class scores for a total of J classes at a time step t, a softmax layer comprising of the linear transformation of is added on top of the last LSTM layer L to estimate the posterior probability p j of the j ‐th class as follows: pj=italicsoftmax()htL=exp()ujT0.25emhtL+bjjjexp()ujT0.25emhtL+bj …”
Section: Situation‐centered Goal Reinforcement Frameworkmentioning
confidence: 99%
“…Kim et al . [KKK*17] proposed an LSTM‐based probabilistic vehicle trajectory prediction approach which uses an occupancy grid map to characterize the driving environment. Deo and Trivedi [DT18] adopt a convolutional social pooling network to predict vehicle trajectories on highways.…”
Section: Applications In Autonomous Drivingmentioning
confidence: 99%
“…In [2], the authors modeled the driver behavior by hidden Markov models (HMM) and Gaussian Process (GP) to generate a group of future trajectories of the predicted vehicle. The long shortterm memory (LSTM) method is utilized in [1] and [3] to analyze past trajectory data and predict the future locations of the surrounding vehicles. [8] proposed to combine a modified mixture density network (MDN) [4] and a conditional variational autoencoder (CVAE) to predict both discrete intention and continuous motions for multiple interacting vehicles.…”
Section: A Motivationmentioning
confidence: 99%